2015
DOI: 10.1007/s13277-014-2963-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of the cancer and adjacent nontumor tissues from cervical squamous cell carcinoma patients by RNA sequencing

Abstract: Cervical cancer is the third most common cancer and the fourth leading cause of cancer deaths among women in the world. The discovery of vital diagnostic and therapeutic markers against cervical squamous cell carcinoma (CSCC) would broaden our understanding on the molecular basis of CSCC. In this study, we thoroughly analyzed the transcriptome of CSCC and matched adjacent nontumor (ATN) tissue. RNA sequencing was performed to screen the differentially expressed genes (DEGs) of three pairs of CSCC and ATN tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…It has been previously demonstrated that HPV infection alone is insufficient for development of cervical cancer; abnormal host genes play an important role in carcinogenesis [62]. The mRNA-based expression profile of normal cervical tissue is known to change during carcinogenesis, and expression of single genes or gene profiles might be used as molecular biomarker to distinguish between different stages of carcinogenesis or indicate response to particular treatment.…”
Section: Other Mrna-based Biomarkersmentioning
confidence: 99%
“…It has been previously demonstrated that HPV infection alone is insufficient for development of cervical cancer; abnormal host genes play an important role in carcinogenesis [62]. The mRNA-based expression profile of normal cervical tissue is known to change during carcinogenesis, and expression of single genes or gene profiles might be used as molecular biomarker to distinguish between different stages of carcinogenesis or indicate response to particular treatment.…”
Section: Other Mrna-based Biomarkersmentioning
confidence: 99%
“…Previous studies have demonstrated the important role of long non-coding RNAs, circular RNAs, microRNAs and mRNAs in cervical cancer development and progression [2][3][4]. High-quality RNA is a pre-requisite for gene expression studies.…”
Section: Main Textmentioning
confidence: 99%
“…The study revealed that SAA1 was upregulated 10 to 60 times in patients with glioblastomas compared with patients with non-neoplastic and other grades of astrocytoma. However, the elevation of SAA1 in serum can be directly correlated with the unfavorable outcomes for many types of cancer such as lung cancer and cervical cancer (Kim et al, 2015;Peng et al, 2015;Sung et al, 2011). The exact concentration of serum SAA1 that serves as the threshold for GBM diagnosis has yet to be determined.…”
Section: ) and Focal Adhesion Assemblymentioning
confidence: 99%
“…Plasma levels of SAA1 are elevated following injury, inflammation, and brain trauma, as well as cancer Milan et al, 2012;Sung et al, 2011;Villapol et al, 2015). A transcriptomic analysis of patients with cervical squamous cell carcinoma revealed that SAA1 levels were associated with tumor size, lymphatic metastasis, and cancer cell invasion (Peng et al, 2015;Ren et al, 2014). SAA1 has also been proposed as a lung cancer biomarker, and patients with lung cancer who have higher levels of plasma SAA1 have less favorable outcomes (Kim et al, 2015;Milan et al, 2012;Sung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%